Consumer Preference Axioms: Behavioral Postulates for Describing and Predicting Stochastic Choice - Hauser, John R. (Management Science, 1978)
This paper draws on econometrics, von Neumann-Morgenstern utility theory, stochastic choice theory, and consumer behavior to develop five basic axioms or postulates of stochastic choice behavior. These axioms imply the existence and uniqueness of a preference function which identifies how consumers evaluate products in terms of product attributes. The preference function produces a scalar goodness measure for each product in a consumer's choice set. These goodness measures then predict choice probabilities for each product in a consumer's choice set. The advantage of these axioms is that they extend the strengths of von Neumann-Morgenstern theory to stochastic choice and make possible the determination of consistent choice probabilities.